SVERI Hostel Management System: A Digital Solution for Streamlined Accommodation and Student Welfare - Bhandare, Harshada; Ghadage, Yashashri; Shinde, Vrushali; Bhapkar, Sneha; Gurav, Dhanlaxmi (International Journal of Computer Sciences and Engineering, 2024)
This project focuses on the managing and maintaining the records of the students who lives in hostel. The project addresses the key functionalities such as room allocation, fee details are tracked automatically of each student in their profiles, provides authentication for which only authorized user have authority for accessing the student data, we can easily update the data in UI, after passed out the batch the system remove their data from user interface to availability of rooms for the new students. By implementing these features improves the efficiency of the hostel. The implementation of this system is expected to reduce administrative workload, enhance resident satisfaction, and provide valuable insights through data analytics. The authentication sure that only authorized users such as rectors or hostel administrators can access data. The interface is designed to allow easy updating of student information and ensure that pass-out batches are removed from the user interface (UI) to free up rooms for new occupants, while retaining historical records in the database for future reference.